Construction Labour Productivity Botrygg Case Studies - Maarof, Aryan; Easeph, Shamim (My University, 2017)
The construction industry in general is a labour centric industry. Labour productivity is a critical factor that determines the success of a construction project. Many researches have pointed out the labour productivity is dependent on working conditions, quality of management and technology. This report aims to measure labour productivity using benchmarking method of projects productivity. It also identifies the factors responsible for the reduction in the rate of labour productivity using the activity analysis, work sampling method and interviews with Botrygg AB’s site manager. Botrygg Bygg AB is both the client and the executive contractor for its projects. The company outsources the design work and does the construction work by itself. The employees are from Romania and are stationed to stay in accommodations which are provided by Botrygg AB and located in a nearby location at their project sites. The research was carried out with the help of methods adopted from the literature review. The literature review covers factors impacting on labour productivity decline from different articles in countries such as Egypt, Kuwait and Sweden. It covers also statistical figures of waste in the construction due to non-value-added activities. These index figures were taken as the foundation base and evident to show a descending trend in labour productivity rate in projects outputs. Two measurement methodologies of productivity benchmarking and activity analysis were reviewed and applied in the empirical part explicitly. Those two methods were adopted in different countries to assess and measure project´s labour productivity. The first method of productivity benchmarking measured the project´ attributes of baseline productivity and project waste indexes (PMI). This methodology was applied on three case study projects of Tyresö, Övre Vasastaden and Fallskärmen to access their labour productivity rates. These projects were executed during three different time periods by Botrygg Bygg AB. The result of this benchmarking indicated a significant decline and remarkable variation in their labour productivity rates. This result was reached by comparing those three projects baseline productivity attributes of (WH/M2) together. To validate this result, the performance metric system of activity analysis was applied on Fallskärmen residential project´s reinforcement task to analyse the laborers direct II work. The analysis involved the site observations and data gathering to identify those unproductive activities which did not add any value on the construction work. The analysis resulted in about 25 % of construction time as value added and 75 % as non-value-added activities. This outcome has negatively impacted on the labour productivity in the entire project. The analysis indicated also many gaps in implementation practice of the reinforcement task elements which have influenced on labour productivity decline. Those gaps which were direct reasons to waste valuable construction time were the laborers walking time empty handed, material movement, waiting for material arrival and equipment set up. Other general impacting factors emerged through the site visits and gathering information from Fallskärmen site manager during interviews. As such the design incompatibility to the sight condition due to different outsourcing of design procurement and the challenge with the ground´s geological condition were issues in pre-construction stage. As well as lack of using buildability by the designers to simplify the design attributes and using of MS Power project software were found as major factors. While the request for information (RFI), type of cast-on-site construction method and logistical delays contributed in reducing the productivity during the construction stage. Also, other factors which had a negative implication on the workforce´s productivity were material quality, overtime work and some human reasons. Based on the gaps detected through applying the activity analysis and weaknesses were found through site visits and interviews, some improvement strategies have been proposed. Those improvements cover both technological and managerial aspects which would increase the work flow and will give access to information when required. Using of BIM as 3D model and adding the 4D of the time function will help the site manager and sub-contractors to understand and tackle conflicts better. BIM use shorten the distance between the project´s potential stakeholders and supplies a closer communication in material delivery. The usage of drones on site will reduce time and can be very fruitful in discussion with designers and monitoring safety and work progress. The managerial recommendations dealt with having design managers meet the site managers while designing, and to provide works incentives to boost their morale. Assigning a well secured Work Breakdown Structure (WBS) prior to deadline of each activity finished or start.
Keywords: Samhällsbyggnadsteknik; Civil Engineering